Observation of Gaussian Pseudorapidity Distributions for Produced Particles in Proton-Nucleus Collisions at Tevatron Energies - Abdurakhmanov Ulugbek; Gulamov Kadyr; Lugovoi Vladimir; Navotny Vadim (Advances in High Energy Physics)
The statistical event-by-event analysis of inelastic interactions of protons in emulsion at 800 GeV reveals the existence of group of events with Gaussian pseudorapidity distributions for produced particles, as suggested by hydrodynamic-tube model. Events belong to very central collisions of protons with heavy emulsion nuclei with probability of realization of less than 1% and with multiplicity of shower particles exceeding (2-3 times) the average multiplicity in proton-nucleus collisions in emulsion. Bjorken’s energy density for these events reaches 2.0 GeV per fm3. The data are interpreted as a result of the QCD phase transition in proton-tube collisions at Tevatron energies.